Innovations in Intelligent Image Analysis - Kwasnicka, Halina; Jain, Lakhmi C.; SpringerLink (Online service) (2011)
This book presents an introduction to new and important research in the images processing and analysis area. It is hoped that this book will be useful for scientists and students involved in many aspects of image analysis. The book does not attempt to cover all of the aspects of Computer Vision, but the chapters do present some state of the art examples.
Advances in Intelligent Image Analysis -- Multi-class Classification in Image Analysis Via Error-Correcting Output Codes -- MORPHOLOGICAL OPERATOR DESIGN FROM TRAINING DATA -- TASK-SPECIFIC SALIENCE FOR OBJECT RECOGNITION -- Fast and efficient local features detection for building recognition -- Visual Perception in Image Analysis -- An Introduction to Magnetic Resonance Imaging: From Image Acquisition to Clinical Diagnosis -- Image Analysis in Poincar -Peters Perceptual Representative Spaces -- Local keypoints and global affine geometry: triangles and ellipses for image fragment matching.
Keywords: Engineering; Artificial intelligence; Engineering; Artificial Intelligence (incl. Robotics).; COMPUTADOR VISIÓN; IMAGE PROCESSING AND COMPUTER VISION; SIGNAL, IMAGE AND SPEECH PROCESSING; COMPUTATIONAL INTELIGENCE